The Perceptions and Participation of Younger Generation in Cirebon Brai Art: A Sufi Psychological Analysis - Muhammad Aziz Husnarrijal; Abdul Muaz; Zubaidi Wahyono (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This article analyses young people's perceptions and participation in practising Cirebon Brai Art using a Sufi psychological approach. The involvement of young people in this study (namely millennials and Gen Z) is to examine the extent to which local wisdom values affect their mental health. The urgency and relevance of this research stem from the fact that millennials' and Gen-Z's interests and attention are largely absorbed by popular art forms that are not deeply rooted in national values. There is also the temptation and addiction to the internet, social media, and online games, which, according to recent findings, have caused mental health problems among young people. Many teenagers, from early adolescence to early adulthood, experience anxiety, depression, and other mental illnesses. This research uses quantitative methods with the research locus at Sanggar Sekar Pusaka Cirebon. The analysis in this study is based on questionnaire and interview results with young respondents involved in Brai art. The findings of this study confirm that the younger generation involved in Cirebon Brai art show positive mental health conditions; their levels of anxiety and depression decrease when they regularly participate in Cirebon Brai art activities. Most young people stated that their spiritual and psychological conditions improved after participating in Brai art. However, the practice of Cirebon Brai art has not received full attention from young people in Cirebon and its surroundings due to a lack of socialisation and seriousness on the part of regional policymakers in West Java.